Smenospongine, a Sesquiterpene Aminoquinone from a Marine Sponge, Induces G1 Arrest or Apoptosis in Different Leukemia Cells - Kong, Dexin (Molecular Diversity Preservation International, 2008)
Smenospongine, a sesquiterpene aminoquinone isolated from the marine sponge Dactylospongia elegans, was previously reported by us to induce erythroid differentiation and G1 phase arrest of K562 chronic myelogenous leukemia cells. In this study, we investigated the effect of smenospongine on the cell cycles of other leukemia cells, including HL60 human acute promyelocytic leukemia cells and U937 human histiocytic lymphoma cells by flow cytometric analysis. Smenospongine induced apoptosis dose-dependently in HL60 and U937 cells. The smenospongine treatment increased expression of p21 and inhibited phosphorylation of Rb in K562 cells, suggesting the p21-Rb pathway play an important role in G1 arrest in K562 cells. However, the p21 promoter was not activated by the smenospongine treatment based on a luciferase assay using the transfected K562 cells. Smenospongine might induce p21 expression via another mechanism than transactivation of p21 promoter.